Ibn ?ajar’s Thoughts On Criticism Of Hadith Narrators: A Study Of The Book Lis?n Al-Miz?n - Yuslem, Nawir; Sulidar, Sulidar; Qomarullah, Muhammad (El-Ghiroh : Jurnal Studi Keislaman, 2024)
This article aims to reveal a hadith scholar ibn ?ajar in assessing the narrators of hadith in the book Lis?n al-M?z?n. His thinking is a way of assessing hadith narrators as an effort to clarify the thoughts of previous scholars such as al-?ahab? in the book Miz?n al-I'tid?l and other scholars who have judged individuals in hadith narrations as d}a?f for various reasons. He has revised the names of the existing but missing narrators (rij?l al-had??) in the sittah book, then explained the names of the unclear or ambiguous hadith transmitters by using explanations such as their real names, nicknames, pseudonym , or father's names and his lineage. From this book he has explained information using codes and symbols as well as additional information which is sometimes just a brief but clear explanation, so that the information from the book is very helpful for hadith experts to know hadith narrators who are foreign to other hadith experts. Ibnu ?ajar advised that the assessment of hadith from the perspective of r?wi must be thorough, so that the assessment of the quality of the hadiths of ?a???, ?asan and ?a?f can be clear and clear by subsequent hadith researchers and not a misjudgment. So, hadith research that is considered to be of weak quality because one scholar has a problem with a r?w? may be of ?iqah or ?ad?q for other scholars because the r?w? is actually a different person.